Creation of a Virtual Tour .Exe Utilizing Very High-Resolution RGB UAV Data - Sefercik, Umut Güneş; Kavzoglu, Taskin; Nazar, Mertcan; Atalay, Can; Madak, Muhammed (My University, 2022)
In the last decades, developments in game engine technology led to a raised attraction to the virtual reality (VR) and augmented reality (AR) concepts which offer users an interactive synthetic environment. Also, with the travel limitations of the current COVID-19 pandemic, VR tour applications that visualize the geospatial data gained popularity more than ever. In this study, a three-dimensional (3D) VR tour application was created for Gebze Technical University (GTU) Campus by integrating unmanned aerial vehicle (UAV) data into an artificial environment by using cross-platform game development engine Unity. For creating high-quality 3D models of the Campus, different imaging geometries and flight altitudes were applied. The aerial photos were achieved with a ground sampling distance (GSD) of ?2.2 cm with a 20 megapixel (MP) Sony Exmor RGB camera. Point cloud processing and the generation of high-quality 3D products were carried out by structure from motion (SfM) based photogrammetric software Agisoft Metashape. Using 86 well-distributed ground control points (GCPs), geometric correction accuracy of ±2 cm (~0.9 pixels) was reached as root mean square error (RMSE). Generated 3D models were imported into the Unity environment and the negative influence of high polygon data on the application performance was reduced by applying occlusion culling and space subdivision rendering optimization algorithms. The visual potential of the VR was improved by adding 3D individual object models such as trees, benches and arbors. For enhancing the information content of the VR tour, interactive information panels including the building metadata such as building name, block name and total floor area were placed. Finally, a first-person player was implemented for a realistic VR experience.
Keywords: Unity; UAV; Virtual Reality; SFM; 3D Textured Mesh Model